2023
DOI: 10.12912/27197050/159729
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Chemical Compositions of Locally Branded Manufactured Cement of Pakistan

Abstract: Cement is a key component of concrete; its qualities impact the properties of concrete created using a particular type of cement. In Pakistan, cement brands are used for an enormous amount. As a result, the cement qualities must fulfill the standards defined by the rules. This research compares the chemical properties of Paidaar, Lucky, DG, Fauji, and Bestway cement brands. This research compares the chemical properties of Paidaar, Lucky, DG, Fauji, and Bestway cement brands. The chemical analysis of cement wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
0
0
Order By: Relevance
“…Mineral admixtures have been suggested as viable RPC cement substitutes. (Muhammad Adil Sultan et al, 2023) (fig. 1).…”
Section: Ordinary Portland Cementmentioning
confidence: 99%
“…Mineral admixtures have been suggested as viable RPC cement substitutes. (Muhammad Adil Sultan et al, 2023) (fig. 1).…”
Section: Ordinary Portland Cementmentioning
confidence: 99%
“…Also, research of four essential components (C3S, C2S, C3A, and C4AF) showed that Paidaar, Lucky, and Fauji cement had less C3S and more C2S, which results in it having the lowest strength when compared to other cement brands. The chemical compositions of several brands were examined, and the Paidaar, Lucky, DG, Fauji, and Bestway cements all fell within the acceptable ranges (Muhammad Adil Sultan et al, 2023).…”
Section: Introductionmentioning
confidence: 98%